ECONSTRUCTION OF 1st JANUARY 2020 STORM IN AN URBAN HOUSING AREA OF TANGERANG SELATAN, INDONESIA - Marelianda, Al Dianty; Frederik, J. Putuhena; Darrien, Y.S. Mah; Rosmina, Ahmad Bustami; Fachrian, Kanafani (Geographia Technica Association, 2021)
The storm in the early hours on the first day of 2020 had recorded the highest intensity of rainfall since 1996. It deluged Jakarta as the capital city of Indonesia and the surrounding satellite cities which including Tangerang Selatan. An urban housing area in Tangerang Selatan, located adjacent to the Ciputat river is selected as study area. The area was affected by floods since the urban housing was established. The United States Environmental Protection Agency’s Storm Water Management Model version 5.1 was used for finding out the hydrological and hydraulic problems. The model indicated that the flows from the sub-catchments did not contribute to cause flood. It was discovered that backwater effects occurred in the Ciputat river was the main cause of flooding. Thus, the existing drainage channels were overwhelmed by additional flow from the river.